Systematic investigation of the wavelength-dependent upconversion enhancement induced by single plasmonic nanoparticles - Yi, Gao (2020)
A convenient method was developed to systematically study the wavelength-dependent upconversion enhancement induced by single plasmonic nanoparticles to overcome unavoidable variations of nanoparticle geometry in practical synthesis techniques. Gold nanospheres and gold nanotriangles coupled to an upconversion nanoparticle monolayer were selected to compare emission and excitation resonance couplings, respectively. The emission intensity of a upconversion nanoparticle monolayer coupled with gold nanospheres (i.e., emission coupling) was found to be slightly lower than that of a reference upconversion nanoparticle monolayer, independent of pumping power. In turn, the emission intensity of a upconversion nanoparticle monolayer coupled with a gold nanotriangle (i.e., excitation coupling) showed an enhancement factor of the emission intensity of about 3.26 at low pumping power, which decreased to 0.48 at high pumping power because of a local heating effect. Our method could provide a convenient strategy for massive data collection of coupled upconversion nanoparticles and plasmonic nanoparticles in a single-particle level and a guideline for systematic investigations involving plasmonic nanoparticles.